Perancangan Elemen Interior Musikal - Filipus Priyo Suprobo, Sherly Widyawati Yusita Kusumarini (Intra, 2014)
Musical Interior Elements are the Interior elements which its function combined with the function of musical instruments. The Interior elements is include floor, wall, ceiling and the element inside it such as furniture. Musical interior elements aims to propose a non-visual aspects of the interior elements of the sound that is produced by the material. The target of this musical is all ages so the design must be easy to play, therefore musical interior designed with a simple form that is easy to play. To convey what it is not enough musical interior elements designed on paper only because the author uses a 1:1 prototype. The design method used is the method of experiment and research on related objects, namely the interior elements and musical instruments to get the opportunities or possibilities of any interior elements that can be combined with the function of musical instruments.